Results of an Interim Analysis of a Prospective Multicenter Study Assessing Radiographic and Patient Outcomes Following Triplanar Tarsometatarsal Arthrodesis with Early Weightbearing - Robert D. Santrock MD; Daniel C. Farber MD; Abdi Raissi MD; Avneesh Chhabra; Jennifer Koay; Paul Dayton MS, DPM; Daniel J. Hatch FACFAS; Jody McAleer DPM, FACFAS; Dane K. Wukich MD; Robert P. Taylor; Deidre Kile (Foot & Ankle Orthopaedics, 2022)
Category: Bunion; Midfoot/Forefoot Introduction/Purpose: The majority of hallux valgus corrections are performed via a two dimensional approach with 1st metatarsal osteotomy and translation in the transverse plane. This approach has demonstrated high long-term recurrence rates. Recent research demonstrates that 87% of hallux valgus deformities are three-dimensional with abnormal frontal-plane rotation of the metatarsal, which cannot be completely addressed with a two dimensional metatarsal osteotomy alone. While correction at the 1st tarsometatarsal (TMT) joint may provide the optimal surgical approach for 3D anatomic restoration at the apex of the deformity, 1st TMT fusion historically entails an extended period of non-weightbearing. This study evaluated the clinical, radiographic, and patient-reported outcomes in patients undergoing instrumented triplanar 1st TMT arthrodesis (TMTA) with a biplanar plating system and protected near-immediate weightbearing. Methods: This is a prospective multicenter study that will continue for 60 months post-operatively. Patients between 14-58 years old with symptomatic hallux valgus (intermetatarsal and hallux valgus angles between 10.0-22.0° and 16.0-40.0°, respectively) and no prior hallux valgus surgery on the operative foot were eligible for this study. Patients were treated with an instrumented TMTA procedure using a biplanar plating system with protected near-immediate weightbearing. Several outcomes (radiographic, return to weightbearing and activities, pain measured by visual analog scale (VAS), Manchester-Oxford Foot Questionnaire (MOxFQ), and Patient Reported Outcomes Measurement Information System (PROMIS)) were evaluated post-operatively. Two independent fellowship trained musculoskeletal radiologists reviewed all radiographic data. These interim results are limited to patients completing at least 6 months of follow-up. Results: 165 patients underwent TMTA with at least 6 months follow-up (mean (SD): 17.8 (7.7); min, max: 5.8, 37.3). Mean age was 41.0 (range:14-58) years; 91.5% of patients were female. Mean (SD) days to protected weightbearing in CAM boot and return to full work were 8.4 (7.7) and 56.8 (45.6), respectively. Significant improvements from baseline in HVA, IMA, and TSP (Table 1), VAS score, MOxFQ and PROMIS domains were observed as early as 6 weeks post-procedure. At 12 months, mean (95% CI) change in VAS was -3.7(-4.0, -3.3); Walking/Standing (MOxFQ) change was -35.2 (-39.6, -30.8); and Physical Function (PROMIS) change was 8.7 (7.1, 10.3). Fifteen (9.1%) patients experienced hardware complications, yet maintained radiographic correction to date. No patients (0/58) with 24 months follow-up have experienced recurrence. Conclusion: These interim findings support that TMTA with biplanar plating is successful in correcting the 3D hallux valgus deformity with early return to weightbearing while demonstrating favorable clinical and patient-reported outcomes. Patients exhibited meaningful pain reduction after surgery and were able to return to full, unrestricted work and activities in less than two months, on average. Statistically significant improvements in patients' health-related quality of life were observed at 6 and 12 months, post-operatively. Patients will continue to be followed for up to 60 months with additional evaluations for complications, 24-month recurrence, and patient satisfaction.